Interfaith Encounter and Religious Pluralism: J. T. Underland’s Mission to Brahmo Samajes of India, 1895-96 - Teed, Paul (American Studies, 2009)
This article examines Jabez T. Sunderland’s mission to the Brahmo Samajes of India in 1895-96 as an example of the changing relationship between American missionaries and India during the late nineteenth century. Built upon the premise that liberal Christianity was the natural fulfillment of the world’s religious development, Sunderland intended to spread the gospel of American Unitarianism among the elite, religious reformers of the Brahmo Samaj. Once in India, however, Sunderland found that the religious culture of the Brahmo Samajes was not simply a reflection of Western thought but rather retained distinctive elements of Hindu tradition. Remarkably, Sunderland and his Brahmo hosts were able to move beyond their differences and formed an alliance based upon shared commitment to religious modernism, social reform and democracy. The article argues that Sunderland’s later career as an influential American advocate of India’s freedom was based on his encounters with the Brahmos in 1895-96.